2012
DOI: 10.1007/978-3-642-33293-7_21
|View full text |Cite
|
Sign up to set email alerts
|

On Tractable Parameterizations of Graph Isomorphism

Abstract: The fixed-parameter tractability of graph isomorphism is an open problem with respect to a number of natural parameters, such as tree-width, genus and maximum degree. We show that graph isomorphism is fixed-parameter tractable when parameterized by the tree-depth of the graph. We also extend this result to a parameter generalizing both tree-depth and max-leaf-number by deploying new variants of cops-androbbers games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Since G\A contains the ≤-maximal elements, they are all incomparable. By definition of an elimination order to degree d, this means that each vertex in G\A has at most d neighbours in G\A, so this graph has degree at most d, establishing (2).…”
Section: Proposition 43 a Graph G Has Ed D (G) ≤ K If And Only If mentioning
confidence: 96%
See 3 more Smart Citations
“…Since G\A contains the ≤-maximal elements, they are all incomparable. By definition of an elimination order to degree d, this means that each vertex in G\A has at most d neighbours in G\A, so this graph has degree at most d, establishing (2).…”
Section: Proposition 43 a Graph G Has Ed D (G) ≤ K If And Only If mentioning
confidence: 96%
“…On the other hand, GI has been shown to be FPT when parameterized by eigenvalue multiplicity [5], tree distance width [21], the maximum size of a simplical component [19,20] and minimum feedback vertex set [12]. Bouland et al [2] showed that the problem is FPT when parameterized by the tree depth of a graph and extended this result to a parameter they termed generalised tree depth. In a recent advance on this, Lokshtanov et al [14] have shown that graph isomorphism is also FPT parameterized by tree width.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To prove the lemma, at first, it is not clear at all how modulo-counting quantifiers can be used to count the number of components satisfying a given FO+MOD-sentence. But it is shown in [2,Lem. 7] that the number of tree-depth roots of each component of a graph is bounded in terms of its tree-depth.…”
Section: Order-invariant Monadic Second-order Logicmentioning
confidence: 96%